A report of high triglyceride level in cord blood of Iranian newborns - Seyed Ali Naghi Kazemi (International Journal of Preventive Medicine, 2013)
Background: Since cord blood triglyceride level have been reported very different in recent articles, the purpose of this study is determination of triglyceride level in cord blood of Iranian newborns and compare it with other reports. Methods: In this study, cord blood of 174 healthy term newborn infants (97 girls, 77 boys) born from healthy mothers have been used. Triglyceride level has been measured by calorie metric method Statistical analysis was performed by independent t test, Mann-Whitney regression test and Spearman correlation coefficient method using SPSS 16 .0 software (SPSS, USA). Results: The mean of cord blood triglyceride was 1.37 ΁ 4.81 mg /dl and there was no statistical difference between two sexes. There was not exist linear relationship between triglyceride and weight, height, head circumference, body mass index and sex of the babies .In 8.6% of our new born infants, triglyceride levels were more than 95th percentile of triglyceride level reported in Iranian population. In 33.9% of our cases, triglyceride levels were more than 95 th percentile of triglyceride level reported in the Nelson text book of Pediatrics. In this study, the 95th percentile of triglyceride level in cord blood was 132.5 mg /dl. Conclusion: The mean and 95 th percentiles of triglyceride levels in cord blood of our newborn infants were higher than other reports. We recommend that larger studies should be conducted in this area to establish preventive ways for increasing epidemic of the metabolic syndrome.